Unveiling the Hidden Risks: Herbal Medicine-Induced Renal Damage – A Case Series Analysis - Ashok Bhat; Rohan Desai; Mahesha Vankalakunti (Case Reports in Nephrology and Dialysis)
Introduction: Herbal medications have been utilized for centuries to treat various ailments, yet their potential to induce renal damage is often underestimated. The popularity of herbal remedies, especially in rural India, stems from cultural beliefs in their holistic healing properties. Case Presentations: This case series comprises 4 patients exhibiting varied renal presentations linked to herbal medication usage. Notably, oxalate nephropathy emerged as a predominant finding. Through comprehensive clinical assessments and renal biopsies, we elucidated the pathophysiological mechanisms underlying herbal nephrotoxicity. Timely recognition and discontinuation of the offending herb, alongside tailored therapeutic interventions like corticosteroid administration, facilitated favourable patient outcomes. Conclusion: These cases underscore the importance of considering herbal remedies as potential culprits in renal dysfunction, particularly in regions where their usage is prevalent. Our findings emphasize the imperative for healthcare practitioners to proactively inquire about herbal medication use in patients with renal failure. Heightened awareness and further research into the safety and mechanisms of herbal nephrotoxicity are essential for optimizing patient care and preventing herb-induced kidney injury.